ip100809_elic_VerbalForms_Medial_zaleztj - Ирина Пайковна Кошкарёва (Туглакова); Олеся Ханина (Bernard Comrie, 2010)
О.Ханина собирает с И.П.Кошкаревой лично-числовую парадигму аориста медиального глагола tedus- 'залезть' O.Khanina collects with I.P.Koshkarjova person-number paradigm of the Aorist of the medial verb tedus- 'to climb (pfv)' Language_Name: Enets Language_Region: Asia Language_Country: Russia Project_Status: Complete Year: 2007 Start_Date: 2008-02-01 End_Date: 2011-01-31 Title ip100809_elic_VerbalForms_Medial_zaleztj